Robotic assistance for autism: a literature review - Ferrão, Isadora; Romero, Roseli; Ramos, Josue; Azevedo, Helio (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2020)
Intervention programs can be introduced to childhood so that children with autism spectrum disorder can improve their disabilities and have a better quality of life as they grow up. In this paper, the research in the area of autism supported by robotics is addressed Based on our literature review, three points deserve to be highlighted: diversity in the research lack of contributions in autism‘s stereotyped focus, behavior deficiency and reduced duration of interaction experiments. The results of this work can assist researchers in determining future directions and also inform and raise awareness of the population about autism, tools and existing technologies. Index Terms—Human-robot interaction, Robotics for children with autism, Social robotics.